Função sexual de mulheres com doença renal crônica - Marques, Bethânia Buzato (2018)
Chronic kidney disease (CKD) is highly prevalent and is currently a worldwide public health problem. It entails physical and psychological consequences and requires adaptation and change of lifestyle. Also, alterations in sexual function of men and women affected by such a disease, as well as decrease in libido are found in both sexes. Objective: to evaluate the performance and sexual satisfaction of women with chronic kidney disease and compare levels of performance and sexual satisfaction in the two main modalities of renal replacement therapy – hemodialysis and renal transplantation. Method: a descriptive cross-sectional study with 49 women enrolled in renal replacement therapy modalities (hemodialysis and renal transplantation) at Hospital de Base in the city of São José do Rio Preto - SP. For data collection, it was used data sheet containing socio-demographic information, scale for evaluation of sexual activity in women (SQ-F) and semi-structured interview. Results: 65,3% of collaborators have reported intense changes in body image after CKD, as well as decrease in libido and sexual performance. About 89,8% of collaborators present impairement in the SQ-F question regarding sexual desire. In the comparison between treatments, difference was significant in all SQ-F, except for question related to pain. When the total score of the instrument was evaluated, the group undergoing hemodialysis achieved a mean score of 39,0 (poor to unfavorable), and the kidney transplant group 70,0 (regular to good). Transplant collaborators has nine times greater chance (odds ratio – 9,2) of achieving better score in the instrument. Conclusion: the performance and sexual satisfaction of women with chronic kidney disease are impaired, which may be associated with different factors. In the comparison between groups, this study demonstrated significantly better sexual functioning in the transplant group.